Situation Report: Hungary, 16 October 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Changes in Economic Regulators Hinted at A Significant Step toward "Reprivatization" in Retail Trade Austrians Use Hungarian Road as Short Cut Skilled Workers Admitted to Universities without High School Diplomas Public Interest Focuses on Ecology Shortage of Implements Lowers Output of Small Gardens Increased Co-operation with Western Pesticide Manufacturers Coverage of Middle East Conflict - II